Coupled techniques for the simulation of fluid-structure and impact problems - Birnbaum, Naury K.; Francis, Nigel J.; Gerber, Bence I. (Computer Assisted Methods in Engineering and Science, 1999)
The ability to model the different regimes of a physical event using different numerical techniques has a number of advantages. Instead of applying the same general solver to all domains of a problem, a solver optimized for a particular regime of material behavior may be used. Thus, in a single analysis, one type of solver may be used for fluid behavior while another type is used for solid/structural response. The various domains in the problem are then coupled together in space and time to provide an efficient and accurate solution. Examples in the use of Eulerian, Lagrangian, Arbitrary Lagrange Eulerian (ALE), Structural, and Smooth Particie Hydrodynamic (SPH) techniques, in various combinations, will be applied to general problems in fluid-structure interaction and impact problems. The relative advantages and limitations of such coupled approaches will be discussed. Examples include the following:• fluid dynamics, blast, impact/penetration (Euler), • hypervelocity impact onto spacecraft shields (Lagrange-Lagrange), • buckling of a thin walled structure (Structural), • impact and penetration of a projectile onto concrete (SPR-Lagrange, Lagrange-Lagrange, EulerLagrange). Numerical results are presented with comparison against experiment where available.